E-HRM usage and value creation: Does a facilitating context matter? - Huub Ruël; Harry van der Kaap (Zeitschrift für Personalforschung (ZfP), 2012)
Electronic Human Resource Management (e-HRM) is assumed to be a driving force behind HRM value creation. However, the issue remains of whether empirical evidence supports this assumption. Moreover, is the relationship straightforward and direct or is it conditional, and do contextual factors intervene? This paper presents a study on this issue. Data was collected through a survey conducted in three international firms using e-HRM applications. The findings suggest that e-HRM usage in line with the system's intended purpose and the contextual factors facilitating e-HRM usage are positively related to HRM value creation. Facilitating contextual factors are positively related to HRM value creation as well, but they also moderate the relationship between e-HRM usage and HRM value creation. However, this moderation is the opposite to what was hypothesized: if the facilitating contextual factors are high, then the relationship between e-HRM usage and HRM value creation is weaker. This finding needs further investigation to clarify the intervening role of contextual factors. – – Das Elektronische Personalmanagement (e-HRM) ist angeblich eine treibende Kraft der Wertschöpfung durch das Personalmanagement. Fraglich ist allerdings, ob empirische Daten diese Annahme unterstützen. Dabei stellt sich die Frage, ob die Verbindung zwischen e-HRM und Wertschöpfung direkt oder konditionell bedingt ist, d.h. ob Kontextfaktoren eine Rolle spielen. Die vorliegende Arbeit geht dieser Frage nach. Dazu wurden Daten mit Hilfe einer Umfrage in drei internationalen Firmen mit e- HRM-Anwendungen erhoben. Die Resultate deuten darauf hin, dass e-HRM positiv mit der Wertschöpfung im Personalmanagement zusammenhängt. Die unterstützenden Kontextfaktoren haben ebenfalls eine positive Verbindung zur Wertschöpfung im Personalmanagement, aber sie moderieren auch die Verbindung zwischen der e- HRM-Anwendung und der Personalmanagement-Wertschöpfung. Anders als angenommen, bewirkt die Moderation allerdings nicht, dass bei hohen Werten der unterstützenden Kontextfaktoren die Verbindung zwischen e-HRM-Anwendung und Wertschöpfung ebenfalls hoch ist. Dieses Ergebnis sollte weiter untersucht werden, um den Einfluss der Kontextfaktoren zu klären.
Keywords: M12; M15; M10; 650; e-HRM; e-HRM usage; HRM; HRM value creation; Elektronisches Personalmanagement; Betriebliche Wertschöpfung; Mehrebenenanalyse (Statistik)